2019
DOI: 10.1108/jima-01-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

“Is this restaurant halal?” Surrogate indicators and Muslim behaviour

Abstract: Purpose The purpose of this study is to investigate what cues or surrogate indicators Muslims use to determine whether restaurants are suitable for dining purposes in the absence of the halal logo and to examine if the cues used are different among Muslims from non-Muslim countries as opposed to Muslims from Muslim countries. Design/methodology/approach Data were collected via semi-structured interviews in one Muslim majority (Malaysia) and one non-Muslim country (the UK). A total of 16 adults participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 58 publications
1
24
1
Order By: Relevance
“…Recent developments show that Muslim customers tend to patronize non-halal certified food premises. Khan and Khan (2019a, 2019b) stated that non-halal certified restaurants serving international cuisine attracted many Muslim customers due to the growing popularity of international cuisine. A non-halal certified restaurant manager revealed that using Muslim staff positively influenced the restaurant’s perceived image among Muslims, thus increasing the restaurant’s attractiveness to Muslim customers (Rosnan et al , 2015) which may affect the customers’ intention to return (Mohd Yusof et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments show that Muslim customers tend to patronize non-halal certified food premises. Khan and Khan (2019a, 2019b) stated that non-halal certified restaurants serving international cuisine attracted many Muslim customers due to the growing popularity of international cuisine. A non-halal certified restaurant manager revealed that using Muslim staff positively influenced the restaurant’s perceived image among Muslims, thus increasing the restaurant’s attractiveness to Muslim customers (Rosnan et al , 2015) which may affect the customers’ intention to return (Mohd Yusof et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the same field of study, hardly any publication explains Muslim customers’ retention behaviour in non-halal certified restaurants. For Muslims, it is an obligation to consume halal products; however, non-halal-certified restaurants are still popular with Muslim consumers (Khan and Khan, 2019a, 2019b). For these reasons, the authors of the current study intended to fill this gap by revealing factors influencing Muslim retention towards non-halal certified restaurants.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of Muslim customers is selected to be another attribute of this study. The results of a previous study show that restaurant attributes become a reliable indicator for Muslims to dine in restaurants without the Halal logo (Khan & Khan, 2019a). Hence, the hypothesis is:H5a: Restaurant attributes as a moderator will strengthen the factors (attitude, subjective norm, PBC, and religiosity) towards the intention of Muslim travellers to patronise the Halal Certified Restaurant H5b: Restaurant attributes as a moderator will strengthen the factors (attitude, subjective norm, PBC, and religiosity) towards the intention of Muslim travellers to patronise the Muslim Friendly Restaurant…”
Section: Restaurant Attributesmentioning
confidence: 97%
“…Due to the lack of Halal food, they tend to be more adaptable to the current conditions at the destinations. They do not mind eating at MFR, primarily vegetarian and seafood restaurants (Khan & Khan, 2019a). On the other hand, another group of travellers will only patronise restaurants with Halal certification.…”
Section: Introductionmentioning
confidence: 99%
“…Only 4.3 percent of Thailand's 69 million people are Muslim. This shows that Thailand's strong position in the global halal industry is due to the tourism industry, which helps to improve halal branding, uniformity of halal definitions and standards, as well as effective support for local Small and Medium Enterprises (Khan, 2019).…”
Section: Food and The Modern Human Psychological Challengementioning
confidence: 99%